A Black Woman Character's Trauma In Racist Society: A Thorough Reading On Faulkner's “That Evening Sun” - Sumaryani, Sri (English Education Department, Universitas Islam Indonesia, 2011)
This paper discusses a black woman character named Nancy in Faulkner's “That Evening Sun” who experiences trauma as the accumulation of her constant fear. The analysis is conducted by using Fanon's theory of psychological trauma in colonial society. The researcher used descriptivequalitative method as it is a qualitative research in which data are nonnumeric. The analysis examines Nancy's unconsciousness resulted in a trauma. It also highlights Faulkner's technique to compare fear experienced by Blacks and Whites. Based on the analysis, Nancy's fear is sourced from her husband's harsh treatments because she is pregnant with a white man's child. Her husband's violent treatments are the manifestation of his disappointment and anger towards his racist surroundings. Nancy's acute fear is worsened by her surroundings' treatment that mostly consist of white Southerners and are apathetic towards her fear. The crippling fear accumulates into trauma. Faulkner's method to contrast the fear experienced by Whites and Blacks are effective to show that the level of fear felt by Blacks is greater than that of Whites.